2017
DOI: 10.1016/j.apj.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy: Legal and neuroscientific aspects

Abstract: Psychopathy is characterised by emotional disturbances that affect interpersonal behaviour and decisionmaking. The objective of this paper is to review the most recent contributions to the field of neuroscience of psychopathy and the implications that this disorder has on the criminal legal field. In regards to this last aspect, we evaluate the issue of psychopaths' accountability and the incidence of psychopathy in many other penal institutions. In terms of the contributions of neuroscience, we will focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 75 publications
(79 reference statements)
0
9
0
1
Order By: Relevance
“…In contrast, findings from this study indicated that having a history of TBI and sociodemographic factors did not significantly predict the grandiose manipulation dimension. This was surprising as previous research has noted the association between early TBI and manipulative traits (Ortega-Escobar et al, 2017). However, Bezdjian et al (2011) found that lack of guilt and grandiose traits may not fully develop until later adolescence.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast, findings from this study indicated that having a history of TBI and sociodemographic factors did not significantly predict the grandiose manipulation dimension. This was surprising as previous research has noted the association between early TBI and manipulative traits (Ortega-Escobar et al, 2017). However, Bezdjian et al (2011) found that lack of guilt and grandiose traits may not fully develop until later adolescence.…”
Section: Discussionmentioning
confidence: 85%
“…Pseudo-psychopathy involves damage to the orbito-frontal prefrontal cortex and can lead to manifestations of disinhibition, antisocial personality, affective issues, impulsivity, and poor insight (Sudarsanan et al, 2005). In one study, the earlier the damage occurred with the orbitofrontal and ventro-medial prefrontal cortexes, the more likely that psychopathic behaviors such as emotional dysregulation, lack of empathy, and manipulation were noted (Ortega-Escobar et al, 2017). A clinical neurobiological case providing support for the role that TBI may have in the manifestation of psychopathic traits is Phineas Gage, who suffered trauma to the prefrontal cortex which resulted in significant personality changes consistent with psychopathy such as impulsivity and irresponsibility (Harlow, 1848).…”
Section: Introductionmentioning
confidence: 99%
“…A limit of this meta-analysis is that some case studies contradicted each others' findings. For example, some studies would show that the amygdala was more active in psychopaths during fear conditioning, while other studies would show the opposite (Ortega-Escobara et al, 2017). This limits the conclusivity of the research and weakens the correlation between brain activity and psychopathy.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…Psychopathy, as defined by the American Heritage Dictionary, is a "mental disorder, especially when manifested by antisocial behavior" (Houghton Mifflin Company, 2006). This behavior stems from a psychopath's traits of chronic dishonesty, a lack of emotion, and impulsivity (Ortega-Escobara et al, 2017). Current research suggests that structural differences in the brain are the root causes of the psychopathic traits that are expressed in the antisocial behavior, often criminal behavior, that defines psychopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Otra limitación importante a tener en cuenta es el diseño retrospectivo utilizado para el desarrollo de la investigación, ya que no posibilita predecir la reincidencia de los internos una vez se encuentren en libertad. Por último, los resultados aquí plasmados pueden incentivar los fuertes vínculos, ya existentes, entre la psicopatía y la peligrosidad, que hacen que estos infractores se vean valorados más negativamente por las instituciones jurídico-penales, tal y como recogen Ortega-Escobar et al (2017), pero quedando demostrado en este mismo estudio la complejidad de esta cuestión, la falta de acuerdo al respecto y la necesidad de tener en cuenta todos los avances científicos recientes.…”
Section: Article In Pressunclassified